Dental care needs in cancer patients during COVID-19 pandemic - a review (Research, Society and Development, 2020)
The risk of contamination by SARS-Cov-2 from cancer patients is high due to immunosuppression. The aim of this study is to investigate evidence that demonstrates the treatment needs related to the main diseases that manifest in the oral cavity and also, the fundamentals that support dental care protocols in cancer patients during the COVID-19 pandemic. The study is characterized as a literature review. Search for articles which have been published in Lilacs, PubMed, Scopus and Web of Science databases. The included articles were presented in the English language and addressed the risk and association among COVID-19, cancer and their oral complications, with recommendations for management and treatment of these patients during outbreak times. In addition to the review, studies about oral complications from antineoplastic therapy were also included. 386 studies about cancer, COVID-19 and dental care were considered in the data base. After applying the inclusion and exclusion criteria, 45 articles were considered. Besides articles involving COVID-19, 31 articles involving oral complications from antineoplastic therapy and possible associations between cancer and oral cavity were included. The results revealed that the main oral diseases in cancer patients were mucositis, xerostomia and periodontal disease. Oral complications may be related to a worse evolution of COVID-19. For the management of oral complications, the dentist must be included in the interdisciplinary team to develop strategies for prevention and promotion of oral health. Dental care is crucial to prevent and treat oral lesions resulting from cancer treatment that can affect the prognosis of COVID-19.